Siapa Nama Kamu? Art in Singapore since the 19th Century - Low, Sze Wee (National Gallery Singapore, 2015)
Published to accompany National Gallery Singapore's inaugural exhibition Siapa Nama Kamu?, the catalogue stands on the shoulders of giants to present a survey of Singapore art from the 19th century to the present, charting major themes across broad time periods. Over 400 works of art in a wide range of media are brought together to trace the ebb and flow of the history of Singapore art. Curatorial essays provide insight into the exhibition making, as well as examine the geographical confines of Singapore, the parameters of national identity and margins of time.